2017
DOI: 10.1177/0310057x1704500611
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Regional Anaesthesia before and after the Introduction of a Dedicated Regional Anaesthesia Service Incorporating a Block Room

Abstract: Dedicated regional anaesthesia services incorporating block rooms and/or block teams may facilitate theatre efficiency and improve training in regional anaesthesia. Currently, it is unknown if a dedicated regional anaesthesia service improves the effectiveness of regional anaesthesia. In November 2013, the Royal Brisbane and Women's Hospital established a dedicated regional anaesthesia service comprising a block team and a block room. Pre-intervention (conventional model of care) registry data was retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Many institutions have dedicated RA ‘block rooms’, but measuring effectiveness of this initiative remains elusive. A recent article, published after this study commenced, found that surrogate measures of analgesia, pain scores and opioid consumption were reduced after introduction of a block room 22…”
Section: Discussionmentioning
confidence: 94%
“…Many institutions have dedicated RA ‘block rooms’, but measuring effectiveness of this initiative remains elusive. A recent article, published after this study commenced, found that surrogate measures of analgesia, pain scores and opioid consumption were reduced after introduction of a block room 22…”
Section: Discussionmentioning
confidence: 94%
“…Novel approaches to education and clinical practice should be encouraged. For example, while uncommon in Australia and New Zealand, instituting RA block teams allows for more focused training opportunities with the added benefit of increased workflow efficiency, 11,12 improved block effectiveness as measured by pain scores 13 and decreased failure rate. 12…”
Section: Discussionmentioning
confidence: 99%
“…This service utilises a block room/block team model of care, which has been described previously. 8 Data were entered contemporaneously at the time of the block and used primarily for quality assurance purposes, but also for long-term clinical follow-up of abnormal neurological findings. Ethics approval was sought prior to data analysis, and an ethics exemption was granted by the RBWH human research and ethics committee (LNR/2018/ QRNBW/47772).…”
Section: Methodsmentioning
confidence: 99%